Research on energy-saving optimization strategies of high-power hydrogen fuel cell power systems - ZHU Dan; WANG Han; SHU Chen; NING Shichao; GUO Zhirui; ZHAO Xuan (Xibei Gongye Daxue Xuebao)
Temperature regulation stand and hydrogen consumption as pivotal benchmarks in the assessment of fuel cell vehicle performance. To enhance the thermal control efficiency and fuel economy of high-power fuel cell power systems, this study formulates a model for a high-power hydrogen fuel cell power system. It meticulously scrutinizes the energy consumption of auxiliary components, notably cooling systems, and devises a power allocation strategy founded on fuzzy logic control, ensuring precise temperature control. Introducing a collaborative optimization control approach for heat and power, aimed at minimizing overall hydrogen consumption, constitutes a central aspect of this paper. Leveraging the parameters of a 115 kW fuel cell truck, the study conducts simulation analysis of control and optimization strategies utilizing the Matlab/Simulink platform. Results underscore the superiority of the collaborative optimization control strategy, demonstrating noteworthy 8.04% and 9.9% reduction in equivalent hydrogen consumption per 100 kilometers compared to the power following control strategy. These findings affirm the efficacy of the proposed strategy in optimizing energy consumption.